Protective Property of Scutellarin Against Liver Injury Induced by Carbon Tetrachloride in Mice - Miao, Zhimin; Lai, Yong; Zhao, Yingying; Chen, Lingmin; Zhou, Jianeng; Li, Chunyan; Wang, Yan (Frontiers in Pharmacology, 2021)
Liver injury is a clinical disorder caused by toxins, drugs and alcohol stimulation without effective therapeutic approaches so far. Scutellarin (SCU), isolated from edible herb Erigeron breviscapus (Vant.) Hand. -Mazz., showed potential hepatoprotective effects but the mechanisms remain unknown. In this work, transcriptomics combined with non-targeted metabolomics and 16S rRNA amplicon sequencing were performed to elucidate the functional mechanisms of SCU on carbon tetrachloride (CCl4)-induced liver injury in mice. The results showed that SCU exerted potent hepatoprotective effects against CCl4-induced liver injury by repressing CYP2E1 and IκBα/NF-κB signaling pathway, modulating gut microbiota especially enriching Lactobacillus and regulating the endogenous metabolites involved in lipid metabolism and bile acid homeostasis. SCU originated from a functional food appears to be a promising agent to guard from liver injury.